Association between SARC-F scores and risk of adverse outcomes in older patients with cardiovascular disease: a prospective study at a tertiary hospital in the south of Vietnam - Nguyen, Tan Van; Nguyen, Tuan Dinh; Cao Dinh, Hung; Nguyen, Tuan Dinh; Ngo, Trinh Thi Kim; Do, Dung Viet; Le, Thanh Dinh (Frontiers in Medicine, 2024)
Introduction Older patients typically face elevated mortality rates and greater medical resource utilization during hospitalizations compared to their younger counterparts. Sarcopenia, serving as a prognostic indicator, is related to disability, diminished quality of life, and increased mortality. The SARC-F questionnaire, known for its cost-effectiveness, offers a valuable means of assessing sarcopenia. This study aims to explore the association between SARC-F scores and risk of adverse outcomes in elderly patients with cardiovascular disease at a Ho Chi Minh City hospital. Method Participants aged 60 and above, admitted to the Department of Cardiology - Interventional and Cardiovascular Emergency of Thong Nhat Hospital in Ho Chi Minh City from November 2021 to June 2022, were recruited for the prospective, single-center study. The prognostic outcomes included all-cause death and the initial occurrence of emergency re-hospitalization within 6 months’ post-discharge. The Kaplan–Meier analysis compared the overall survival rates between different SARC-F score groups. Results The study enrolled 285 patients with a median age of 74 (67, 81). During a 6-month follow-up period, there were 14 cases of mortality. A SARC-F score of 4 or higher was significantly associated with an increased risk of all-cause mortality, with HR of 2.02 (95% CI: 1.39–2.92, p < 0.001), and higher incidence of re-hospitalization events with RR of 1.66 (95% CI: 1.06 to 2.59, p = 0.026). Kaplan–Meier survival analysis indicated a notably higher mortality rate in the patients with high SARC-F scores (p < 0.001). Conclusion In elderly patients with cardiovascular disease, the SARC-F questionnaire could serve as a simple and cost-effective method for detecting mortality and the risk of re-hospitalization.